2023
DOI: 10.1097/md.0000000000033206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic frequency distribution of ACE, ADRB1, AGTR1, CYP2C9*3, CYP2D6*10, CYP3A5*3, NPPA and factors associated with hypertension in Chinese Han hypertensive patients

Abstract: We analyzed the polymorphisms of 7 antihypertensive drugs-related genes and the factors associated with hypertension in hypertensive patients of Han ethnicity in Qingyang, China. A total of 354 hypertensive patients of Han ethnicity were enrolled from Qingyang, China. The ACE (I/D), ADRB1 (1165G > C), AGTR1 (1166A > C), CYP2C9*3, CYP2D6*10, CYP3A5*3 and NPPA (T2238C) polymorphisms were assessed. Clinical data of patients was also obtained. The influencing factors of hypertension were evaluated. The genotype fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Additionally, in the province where the study was performed, the diet included a high salt intake, and when the participants were overweight, the risk increased, suggesting a correlation between diet, obesity, and hypertension ( 34 ). These results align with those of Wang et al ( 32 ), where a correlation between a high-salt diet and increased hypertension prevalence was described ( 32 ). More studies regarding the impact of rs4343 have been performed for different populations, including samples from Europe, and Asia, with similar outcomes, associating rs4343 with an increased hypertension risk ( 35 ).…”
Section: Influence Of the Ace Polymorphisms On Hyp...supporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, in the province where the study was performed, the diet included a high salt intake, and when the participants were overweight, the risk increased, suggesting a correlation between diet, obesity, and hypertension ( 34 ). These results align with those of Wang et al ( 32 ), where a correlation between a high-salt diet and increased hypertension prevalence was described ( 32 ). More studies regarding the impact of rs4343 have been performed for different populations, including samples from Europe, and Asia, with similar outcomes, associating rs4343 with an increased hypertension risk ( 35 ).…”
Section: Influence Of the Ace Polymorphisms On Hyp...supporting
confidence: 93%
“…Hypertension incidence is growing worldwide, and factors such as population aging, obesity, and an unhealthy diet, further increase the issue ( 7 , 41 ). Furthermore, the genetic composition of a population could also significantly increase hypertension predisposition ( 32 ), highlighting the importance of gene–environment interactions involved in this disease. Moreover, LMICs are the most affected by the increase in hypertension prevalence, with more than 1.04 billion people living with this disease in these regions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed that CYP2D6∗10 , AGTR1 ( 1166A > C ), and NPPA ( 2238T > C ) genes do not conform to the Hardy–Weinberg equilibrium test. Another study conducted in Chinese Han hypertensive patients also found that CYP2D6∗10 was not in HWE [ 16 ]; this might be because CYP2D6∗10 , AGTR1 ( 1166A > C ), and NPPA ( 2238T > C ) genes were associated with the development of hypertension [ 23 , 35 , 36 ]. Studies revealed that alleles associated with disease etiology often deviate from the expected allele or genotype frequency [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Персонализированная фармакотерапия АГ, основанная на различных вариациях генов, ответственных за функцию метаболических ферментов лекарственных средств (ЛС), генов, которые вовлечены в патогенетические механизмы развития АГ и изменяют фармакодинамические эффекты ЛС [2][3][4][5], а также генов, связанных с переносчиками ЛС, позволит повысить эффективность фармакотерапии АГ у пациентов, регулярно получающих антигипертензивные препараты (АГП) в соответствии с клиническими рекомендациями и при этом не достигающих целевых цифр артериального давления (АД) [6][7][8].…”
Section: Introductionunclassified